Using social media big data with machine learning to improve customer satisfaction - Demir, Hilal. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
With the increasing importance of customer relationship management and improving customer support in today's competitive business landscape, there is a growing need to leverage machine learning techniques for gaining insights, forecasts, and better decision-making. Sentiment analysis, in particular, has emerged as a powerful tool for improving customer support services. In this study, we explore the use of three gradient boosting algorithms, XGBoost, CatBoost, and LightGBM, for sentiment classification on Twitter data. We employ ensemble classifications to analyze the sentiment of the data and observe improvements in performance. Our results are compared to other two algorithms that are popularly used in the context of sentiment analysis and show that the ensemble classification of the three algorithms yields the highest accuracy and F1 score. By addressing the gap in understanding how different machine learning algorithms can be used to enhance customer support processes, this research aims to contribute to the improvement of customer satisfaction and loyalty. Specifically, the study aims to improve the accuracy of sentiment classification, thereby enabling businesses to better meet customer expectations for fast and efficient customer support.
Keywords: Consumer satisfaction.; Social media.; Machine learning.